CYP2D6 genotype analysis of a Thai population: platform comparison. (11th July 2018) - Chamnanphon, Monpat; Gaedigk, Andrea; Vanwong, Natchaya; Nuntamool, Nopphadol; Hongkaew, Yaowaluck; Puangpetch, Apichaya; Sukasem, Chonlaphat
The highly polymorphic CYP2D6 gene locus leads to a wide range of enzyme activity. Since there are limited data for Thai, the major aim was to investigate CYP2D6 genetic variation in a large Thai population (n = 920). CYP2D6 genotyping was performed using four different platforms. Genotype call rates of the Luminex xTAG ® and AmpliChip CYP450 test were 96.5% and 87.4%, respectively. Based on Luminex xTAG ® data, the most common alleles and genotypes were * 1 0 (49.6%), *1 (24.6%), *2 (10.8%), *5 (6.7%), *41 (6.5%) and *1/*10 (23.9%), *10/*10 (21.5%), *2/*10 (9.4%), *5/*10 (6.9%), *10/*41 (5.7%), respectively. Challenges and limitations of the platforms evaluated are discussed. These data add to our knowledge regarding interethnic variability in CYP2D6 activity and contribute to improving drug therapy in the Thai.